Implementation of Character Education Through Culture-Based Discipline School Rules at SMP Negeri 4 Kayuagung - Novarini, Rita; Ahyani, Nur; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to analyze the implementation of character education through culture-based discipline in school rules at SMP Negeri 4 Kayuagung. Data collection tools using interviews, documentation, observation and literature review. Data analysis used descriptive qualitative analysis with research stages referring to Miles and Huberman’s theory, namely (1) collecting data, (2) data reduction; (3) data presentation; (4) conclusion. The results of the study stated that the implementation of character education through a culture of discipline carrying out discipline at SMP Negeri 4 Kayuagung was carried out in 3 stages, namely (1) Implementation of character education through the preparation of rules and regulations at SMP Negeri 4 Kayuagungyang; (2) Implementation of character education through the implementation of school rules; (3) Evaluation of the implementation of discipline at SMP Negeri 4 Kayuagung. Broadly speaking, the obstacles faced come from family factors, school environmental factors, and community environmental factors.